Performance of worldwide interoperability for microwave access (WIMAX) in non line of sight and multipath environment - Abas Azmi, Khairul Bariah (2007)
The requirement of BWA to operate in the non line of sight and multipath environment has lead to the amendment of IEEE 802.16 standard. The amended standard which is 802.16a covers fixed BWA in the spectrum of 2 to 11 GHz has become a stepping stoned to the enhancement of the wireless broadband technology. A discrete channel model based on the Stanford University Interim (SUI) model was used in the standard. This project evaluates the effect of empirical models on the 802.16a physical layer performance at 3.5 GHz. The empirical propagation model used in the project are COST 231[8] and ECC 33 model[9]. The comparison of the system performance of the OFDM between SUI, COST 231 and ECC 33 model were evaluated in terms of bit error rate (BER). The simulation results of these propagation model on 802.16a physical layer specification were used to validate their applicability in urban, suburban and rural environment.